2017
DOI: 10.1037/spq0000178
|View full text |Cite
|
Sign up to set email alerts
|

The relative contribution of subjective office referrals to racial disproportionality in school discipline.

Abstract: To improve our understanding of where to target interventions, the study examined the extent to which school discipline disproportionality between African American and White students was attributable to racial disparities in teachers' discretionary versus nondiscretionary decisions. The sample consisted of office discipline referral (ODR) records for 1,154,686 students enrolled in 1,824 U.S. schools. Analyses compared the relative contributions of disproportionality in ODRs for subjectively and objectively def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
98
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 219 publications
(102 citation statements)
references
References 38 publications
(50 reference statements)
3
98
1
Order By: Relevance
“…Studies typically measure behavior in three ways: (a) the type of infraction committed (e.g., attendance, disruption, fighting, drug possession), (b) the frequency of misbehavior (e.g., first offense or repeated offenses), and (c) the disciplinary outcomes (e.g., suspensions and expulsions). Several studies have data on the reasons for referral and can pinpoint the behaviors that lead to disciplinary outcomes (Anyon et al, 2014; Girvan, Gion, McIntosh, & Smolkowski, 2017; Huang & Cornell, 2017; Peguero & Shekarkhar, 2011; Rocque & Paternoster, 2011; Smolkowski, Girvan, McIntosh, Nese, & Horner, 2016; Skiba et al, 2002; Skiba et al, 2011; Skiba, Chung, et al, 2014). Some studies link behavior type and frequency to disciplinary outcomes (Huang & Cornell, 2017; Skiba et al, 2011; Skiba, Chung, et al, 2014), and others focus on the behaviors and infractions that initiate the discipline process (ODRs) (Girvan et al, 2017; Rocque & Paternoster, 2011; Smolkowski et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies typically measure behavior in three ways: (a) the type of infraction committed (e.g., attendance, disruption, fighting, drug possession), (b) the frequency of misbehavior (e.g., first offense or repeated offenses), and (c) the disciplinary outcomes (e.g., suspensions and expulsions). Several studies have data on the reasons for referral and can pinpoint the behaviors that lead to disciplinary outcomes (Anyon et al, 2014; Girvan, Gion, McIntosh, & Smolkowski, 2017; Huang & Cornell, 2017; Peguero & Shekarkhar, 2011; Rocque & Paternoster, 2011; Smolkowski, Girvan, McIntosh, Nese, & Horner, 2016; Skiba et al, 2002; Skiba et al, 2011; Skiba, Chung, et al, 2014). Some studies link behavior type and frequency to disciplinary outcomes (Huang & Cornell, 2017; Skiba et al, 2011; Skiba, Chung, et al, 2014), and others focus on the behaviors and infractions that initiate the discipline process (ODRs) (Girvan et al, 2017; Rocque & Paternoster, 2011; Smolkowski et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have reinforced these findings (Anyon et al, 2014;Girvan et al, 2017;Huang & Cornell, 2017; Rocque and Paternoster 2011; Peguero & Shekarkhar, 2011;Skiba et al, 2011). For example, Rocque and Paternoster (2011) used school-level data from 45 elementary schools, logistics regression, and negative binomial regression to examine (a) if students received ODRs for misconduct and (b) the number of times students were referred to the office, and they found a significant difference in the likelihood of Black students receiving ODRs and disciplinary action but insisted that discipline disparities were not explained by differences in behavior.…”
Section: Student (Mis)behaviormentioning
confidence: 86%
“…Furthermore, reliance on ODRs as an indicator of discipline is not without concerns. For decades, results from research have found that students of color have been overrepresented in school discipline data (e.g., Girvan, Gion, McIntosh, & Smolkowski, 2017; Skiba, Horner, Chung, Rausch, May, & Tobin, 2011; Skiba, Michael, Nardo, & Peterson, 2002). Recently, Girvan et al.…”
Section: Discussionmentioning
confidence: 99%
“…They use teacher-reported measures of behavior, which still are based on a teacher’s subjective interpretation of a student. Teacher judgments are very likely unconsciously and unintentionally influenced by racial bias (Gilliam, Maupin, Reyes, Accavitti, & Shic, 2016; Girvan, Gion, McIntosh, & Smolkowski, 2016), which limits the validity of Wright et al’s analysis.…”
Section: Literature Reviewmentioning
confidence: 99%